The conservation status of the threatened gazelles of Ar Rub’ al-Khālī, Saudi Arabia - Tim Wacher; Ahmed Alboug; Chris Barichievy; Zaffar Rais Mir; Tom Bruce; David Olson; Rajan Amin (Journal of Arid Environments, 2025)

Nucleation-assisted microthermometry: A novel application to fluid inclusions in halite - William D. Arnuk; Emmanuel Guillerm; Tim K. Lowenstein; Yves Krüger; Kristian J. Olson; Nadav G. Lensky; Achim Brauer (Chemical Geology, 2024)

Unified 200 kyr paleohydrologic history of the Southern Great Basin: Death Valley, Searles Valley, Owens Valley and the Devils Hole cave - Tim K. Lowenstein; Kristian J. Olson; Brian W. Stewart; David McGee; Justin S. Stroup; Adam M. Hudson; Kathleen A. Wendt; Mark D. Peaple; Sarah J. Feakins; Tripti Bhattacharya; Steve Lund (Quaternary Science Reviews, 2024)

Seasonal dynamics of evaporite mineral precipitation, dissolution, and back-reactions in shallow and deep hypersaline lakes - Kristian J. Olson; Robert V. Demicco; Tim K. Lowenstein (Geochimica et Cosmochimica Acta, 2023)

Application of Brillouin thermometry to latest Pleistocene and Holocene halite from Searles Lake, California, USA - Kristian J. Olson; Emmanuel Guillerm; Mark D. Peaple; Tim K. Lowenstein; Véronique Gardien; Frédéric Caupin; Sarah J. Feakins; Jessica E. Tierney; Justin Stroup; Steve Lund; David McGee (Earth and Planetary Science Letters, 2023)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Ecological Metrics of Biomass Removed by Three Methods of Purse‐Seine Fishing for Tunas in the Eastern Tropical Pacific Ocean - TIM GERRODETTE; ROBERT OLSON; STEPHEN REILLY; GEORGE WATTERS; WILLIAM PERRIN (Conservation Biology, 2012)
An ecosystem approach to fisheries management is a widely recognized goal, but describing and measuring the effects of a fishery on an ecosystem is difficult. Ecological information on the entire catch (all animals removed, whether retained or discarded) of both species targeted by the fishery and nontarget species (i.e., bycatch) is required. We used data from the well‐documented purse‐seine fishery for tunas (Thunnus albacares, T. obesus, and Katsuwonus pelamis) in the eastern tropical Pacific Ocean to examine the fishery's ecological effects. Purse‐seine fishing in the eastern tropical Pacific is conducted in 3 ways that differ in the amount and composition of target species and bycatch. The choice of method depends on whether the tunas are swimming alone (unassociated sets), associated with dolphins (dolphin sets), or associated with floating objects (floating‐object sets). Among the fishing methods, we compared catch on the basis of weight, number of individuals, trophic level, replacement time, and diversity. Floating‐object sets removed 2–3 times as much biomass as the other 2 methods, depending on how removal was measured. Results of previous studies suggest the ecological effects of floating‐object sets are thousands of times greater than the effects of other methods, but these results were derived from only numbers of discarded animals. Management of the fishery has been driven to a substantial extent by a focus on reducing bycatch, although discards are currently 4.8% of total catch by weight, compared with global averages of 7.5% for tuna longline fishing and 30.0% for midwater trawling. An ecosystem approach to fisheries management requires that ecological effects of fishing on all animals removed by a fishery, not just bycatch or discarded catch, be measured with a variety of metrics.

International workshop on opportunities for ecosystem approaches to fisheries management in the Pacific Ocean tuna fisheries - Valerie Allain; Simon Nicol; Jeffrey Polovina; Marta Coll; Robert Olson; Shane Griffiths; Jeffrey Dambacher; Jock Young; Jesus Jurado Molina; Simon Hoyle; Tim Lawson (Reviews in Fish Biology and Fisheries, 2012)

Variability of hair coat and skin traits as related to adaptation in Criollo Limonero cattle - Antonio Landaeta-Hernández; Sunny Zambrano-Nava; Juan P. Hernández-Fonseca; Rosario Godoy; Marcos Calles; José L. Iragorri; Lauderys Añez; Miguel Polanco; Merilio Montero-Urdaneta; Tim Olson (Tropical Animal Health and Production, 2011)

Global biogeography and ecology of body size in birds - Valérie A. Olson; Richard G. Davies; C. David L. Orme; Gavin H. Thomas; Shai Meiri; Tim M. Blackburn; Kevin J. Gaston; Ian P. F. Owens; Peter M. Bennett (Ecology Letters, 2009)
In 1847, Karl Bergmann proposed that temperature gradients are the key to understanding geographic variation in the body sizes of warm‐blooded animals. Yet both the geographic patterns of body‐size variation and their underlying mechanisms remain controversial. Here, we conduct the first assemblage‐level global examination of ‘Bergmann’s rule’ within an entire animal class. We generate global maps of avian body size and demonstrate a general pattern of larger body sizes at high latitudes, conforming to Bergmann’s rule. We also show, however, that median body size within assemblages is systematically large on islands and small in species‐rich areas. Similarly, while spatial models show that temperature is the single strongest environmental correlate of body size, there are secondary correlations with resource availability and a strong pattern of decreasing body size with increasing species richness. Finally, our results suggest that geographic patterns of body size are caused both by adaptation within lineages, as invoked by Bergmann, and by taxonomic turnover among lineages. Taken together, these results indicate that while Bergmann’s prediction based on physiological scaling is remarkably accurate, it is far from the full picture. Global patterns of body size in avian assemblages are driven by interactions between the physiological demands of the environment, resource availability, species richness and taxonomic turnover among lineages.

Regional variation in the historical components of global avian species richness - Gavin H. Thomas; C. David L. Orme; Richard G. Davies; Valerie A. Olson; Peter M. Bennett; Kevin J. Gaston; Ian P. F. Owens; Tim M. Blackburn (Global Ecology and Biogeography, 2008)
Aim Using a global data base of the distribution of extant bird species, we examine the evidence for spatial variation in the evolutionary origins of contemporary avian diversity. In particular, we assess the possible role of the timing of mountain uplift in promoting diversification in different regions. Location Global. Methods We mapped the distribution of avian richness at four taxonomic levels on an equal‐area 1° grid. We examined the relationships between richness at successive taxonomic levels (e.g. species richness vs. genus richness). We mapped the residuals from linear regressions of these relationships to identify areas that are exceptional in the number of lower taxa relative to the number of higher taxa. We use generalized least squares models to test the influence of elevation range and temperature on lower‐taxon richness relative to higher‐taxon richness. Results Peaks of species richness in the Neotropics were congruent with patterns of generic richness, whilst peaks in Australia and the Himalayas were congruent with patterns of both genus and family richness. Hotspots in the Afrotropics did not reflect higher‐taxon patterns. Regional differences in the relationship between richness at successive taxonomic levels revealed variation in patterns of taxon co‐occurrence. Species and genus co‐occurrence was positively associated with elevational range across much of the world. Taxon occurrence in the Neotropics was associated with a positive interaction between elevational range and temperature. Conclusions These results demonstrate that contemporary patterns of richness show different associations with higher‐taxon richness in different regions, which implies that the timing of historical effects on these contemporary patterns varies across regions. We suggest that this is due to dispersal limitation and phylogenetic constraints on physiological tolerance limits promoting diversification. We speculate that diversification rates respond to long‐term changes in the Earth's topography, and that the role of tropical mountain ranges is implicated as a correlate of contemporary diversity, and a source of diversification across avian evolutionary history.

Energy, range dynamics and global species richness patterns: reconciling mid‐domain effects and environmental determinants of avian diversity - David Storch; Richard G. Davies; Samuel Zajíček; C. David L. Orme; Valerie Olson; Gavin H. Thomas; Tzung‐Su Ding; Pamela C. Rasmussen; Robert S. Ridgely; Peter M. Bennett; Tim M. Blackburn; Ian P. F. Owens; et al. (Ecology Letters, 2006)
Spatial patterns of species richness follow climatic and environmental variation, but could reflect random dynamics of species ranges (the mid‐domain effect, MDE). Using data on the global distribution of birds, we compared predictions based on energy availability (actual evapotranspiration, AET, the best single correlate of avian richness) with those of range dynamics models. MDE operating within the global terrestrial area provides a poor prediction of richness variation, but if it operates separately within traditional biogeographic realms, it explains more global variation in richness than AET. The best predictions, however, are given by a model of global range dynamics modulated by AET, such that the probability of a range spreading into an area is proportional to its AET. This model also accurately predicts the latitudinal variation in species richness and variation of species richness both within and between realms, thus representing a compelling mechanism for the major trends in global biodiversity.

Optimal time-frequency projections for localized tomography - Tim Olson (Annals of Biomedical Engineering, 1995)